MYTH, RITUAL AND KINGSHIP IN BUGANDA, by Benjamin C. Ray, Oxford University Press, New York, Oxford, 1991,239pp., illus., photos. - Kubik, Gerhard (International Library of African Music, 1996)
pages: 129-132
Keywords: Myth; Ritual; African Music; Uganda; Buganda; Kingship